2020
DOI: 10.1111/apa.15208
|View full text |Cite
|
Sign up to set email alerts
|

Six commonly used empirical body surface area formulas disagreed in young children undergoing corrective heart surgery

Abstract: Aim Formulas for empirical body surface area (BSA), which is used to estimate body size and standardise physiological parameters, may disagree in children. We compared six commonly used BSA formulas—Du Bois, Boyd, Costeff, Haycock, Meban and Mosteller—in a surgical cohort. Methods This retrospective single‐centre cohort study comprised 68 children who had corrective heart surgery at Skåne University Children's Hospital, Lund, Sweden, from February 2010 to March 2017. Results The children (51% female) underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…This is a retrospective study, but consecutive nonselected patients were included. The number of boys was higher than the number of girls, which is related to the known male predominance of TGA 17 …”
Section: Limitationsmentioning
confidence: 84%
See 1 more Smart Citation
“…This is a retrospective study, but consecutive nonselected patients were included. The number of boys was higher than the number of girls, which is related to the known male predominance of TGA 17 …”
Section: Limitationsmentioning
confidence: 84%
“…BSA was calculated with the Mosteller formula, and we do not know if the results from the regression analysis would have been similar if we had used a different BSA formula. However, it has recently been shown that the Mosteller formula provides the most accurate estimate of BSA in young children with congenital heart disease 17 . The fact that BSA is a function of height and weight implies that there is some redundancy in the investigated influence variables, which is expressed in the high correlations between these three variables.…”
Section: Discussionmentioning
confidence: 99%
“…The Mosteller formula has been studied by several papers since it was established in 1987 ( 3 , 27 , 28 ). The greatest competitive advantage of the Mosteller formula is its conciseness.…”
Section: Discussionmentioning
confidence: 99%
“…Indexing is also complicated by the fact that children have a relatively larger body surface area (BSA) compared with body weight (BW) than adults, resulting in a non‐linear‐indexed haemodynamic variables 5 . Empirical formulas used to determine BSA in children often disagree in their calculations, adding to possible errors regarding estimations of indexed haemodynamic variables 6 …”
Section: Introductionmentioning
confidence: 99%
“…used to determine BSA in children often disagree in their calculations, adding to possible errors regarding estimations of indexed haemodynamic variables. 6 In 1963, Jegier and colleges published their landmark paper using dye dilution method, on the relationship between cardiac output (CO) and body size, comparing indexing with BSA and BW. 7 They found that although both size variables had a similar correlation with CO, there was a significant difference between age groups when BSA was used for CO indexing.…”
mentioning
confidence: 99%